2021
DOI: 10.1038/s41392-020-00410-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cystathionine β-synthase promotes apoptosis and reduces cell proliferation in chronic myeloid leukemia

Abstract: Increased endogenous hydrogen sulfide (H2S) level by cystathionine β-synthase (CBS) has been shown to closely relate tumorigenesis. H2S promotes angiogenesis, stimulates bioenergy metabolism and inhibits selective phosphatases. However, the role of CBS and H2S in chronic myeloid leukemia (CML) remains elusive. In this study, we found that CBS and H2S levels were increased in the bone marrow mononuclear cells of pediatric CML patients, as well as in the CML-derived K562 cells and CBS expression levels were corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 68 publications
1
16
0
Order By: Relevance
“…For CML, similar to our analysis, several studies have shown that levels of glutamate, serine, which is a precursor of cysteine, and alanine are increased by CML (153)(154)(155). Consistent with these NEAAs playing an important role in CML, restriction of serine (156,157) and its derivatives glycine (156), or cysteine (158,159) decreases CML proliferation, supporting that targeting these NEAA pathways may be a potential target for CML.…”
Section: Restriction Of Other Neaas Derived From Glutamate Decrease Myeloid Leukemia Proliferationsupporting
confidence: 87%
“…For CML, similar to our analysis, several studies have shown that levels of glutamate, serine, which is a precursor of cysteine, and alanine are increased by CML (153)(154)(155). Consistent with these NEAAs playing an important role in CML, restriction of serine (156,157) and its derivatives glycine (156), or cysteine (158,159) decreases CML proliferation, supporting that targeting these NEAA pathways may be a potential target for CML.…”
Section: Restriction Of Other Neaas Derived From Glutamate Decrease Myeloid Leukemia Proliferationsupporting
confidence: 87%
“…tumorigenic; thus the inhibition of CBS activity in K562 and mononuclear cells isolated from the bone marrows of CML patients using the CBS-inhibitor aminooxy acetic acid (AOAA) lead to an overall reduction in proliferation and the induction of apoptosis in these cells (21).…”
Section: Essential Amino Acids Methioninementioning
confidence: 99%
“…Previously, the effect of endogenous H 2 S inhibition by employing AOAA and PAG on xenograft tumor growth has been reported in human chronic myeloid leukemia and astrocytoma. They observed dramatically decreased tumor growth in the treated animals compared to control [64,65]. Our study showed that PAG, AOAA, and L-Asp significantly inhibited BC xenograft tumor growth, and the combined group showed stronger preventive effects on tumor growth.…”
Section: Discussionmentioning
confidence: 51%